Factors Associated With Oxyhemoglobin Desaturation During Rapid Sequence Intubation in a Pediatric Emergency Department: Findings From Multivariable Analyses of Video Review Data. (16th March 2015) - Rinderknecht, Andrea S.; Mittiga, Matthew R.; Meinzen‐Derr, Jareen; Geis, Gary L.; Kerrey, Benjamin T.; Walthall, Jennifer
Abstract Objectives In a video‐based study of rapid sequence intubation (RSI) in a pediatric emergency department (PED), 33% of children experienced oxyhemoglobin desaturation (SpO2 < 90%). To inform targeted improvement interventions, we planned multivariable analyses to identify patient and process variables (including time‐based data around performance of key RSI process elements uniquely available from video review) associated with desaturation during pediatric RSI. Methods These were planned analyses of data collected during a retrospective, video‐based study of RSI in a high‐volume, academic PED. For variables with plausible associations with desaturation, multiple logistic regression and generalized estimating equations were used to identify those characteristics independently associated with desaturation at both the patient and the attempt levels. Results The authors analyzed video data from 114 patients undergoing RSI over 12 months. Desaturation was more common in patients 24 months of age and younger (59%) than in patients older than 24 months of age (10%). Variables associated with desaturation in patients 24 months of age and younger were duration of attempts (both individual and cumulative), the occurrence of esophageal intubation, a respiratory indication for intubation, and young age. The receiver operating characteristics curve for the model had an area under the curve of 0.80 (95% confidence interval [CI] = 0.67 to 0.92). Forty‐six percent of desaturations occurred after 45 seconds of laryngoscopy, and 82% after 30 seconds. The odds ratio for desaturation on individual attempts lasting longer than 30 seconds (vs. those 30 seconds or less) was 5.7 (95% CI = 2.26 to 14.36). Conclusions For children 24 months of age or younger undergoing RSI in a PED, respiratory indication for intubation, esophageal intubation, and duration of laryngoscopy (both individual and cumulative) were associated with desaturation; the number of attempts was not. Interventions to limit attempt duration in the youngest children may improve the safety of RSI.